Labrorostratus caribensis, a new oenonid polychaete from the Grand Caribbean living in the body cavity of a nereidid, with emendation of the genus - Hernández-Alcántara, Pablo; Cruz-Pérez, Ismael Narciso; Solís-Weiss, Vivianne (Zootaxa, 2015)
Endoparasitic relationships among polychaetes are uncommon and mostly restricted to about 20 species of the family Oenonidae. We herein describe Labrorostratus caribensis, a new oenonid species living in the body cavity of a nereidid polychaete in Chinchorro Bank (Mexican Caribbean). This is the first report of a parasitic relationship between oenonids and nereidids in the Grand Caribbean region. The new species is diagnosed by the jaw apparatus reduced to only maxillary carriers fused, one simple modified ventral chaeta from midbody and lack of acicular spines. The generic diagnosis is emended to include species without maxillary plates. A synopsis of parasitism among polychaetes worldwide is presented.
World Polychaeta Database (WPolyDb)